Stemming the Tide Global Strategies for Sustaining Cultural Heritage through Climate Change - Rushfield, Rebecca (2021)
Climate change has become one of the most significant and fastest growing threats to cultural heritage around the globe. Yet cultural heritage sites and collections also serve as invaluable sources of resilience for communities to address climate change. In March 2020, the Smithsonian American Art Museum and the Smithsonian's National Collections Program convened the symposium "Stemming the Tide: Global Strategies for Sustaining Cultural Heritage through Climate Change" to empower cultural heritage authorities, managers, and advocates to pursue more ambitious engagement and collaborative approaches to climate change. Speakers explored six categories of cultural heritage identified by the International Council on Monuments and Sites (ICOMOS): Cultural Landscapes and Historic Urban Landscapes, Archaeological Sites, Built Heritage (Buildings and Structures), Cultural Communities, Intangible Cultural Heritage, and Museums and Collections.